PALAVRAS LOUCAS, ORELHAS MOUCAS - OS RELATOS DE VIAGEM DOS ROMÂNTICOS BRASILEIROS - SÜSSEKIND, FLORA (Revista USP, 1996)
PALAVRAS LOUCAS, ORELHAS MOUCAS - OS RELATOS DE VIAGEM DOS ROMÂNTICOS BRASILEIROS.